Fatigue of steam turbine blades at resonance conditions. (October 2019) - Rodríguez, J.A.; Castro, L.; Tejeda, A.L.; García, J.C.; Rodríguez, J.M.; Galindo, E.; El Hamzaoui, Y.
Abstract: Different problems are presented in the steam turbines and their components. Rotor blades in the steam turbines are the most important component and, where failures occur frequently, particularly in the blades of the last low-pressure stages (LP) the useful life of the steam turbines is affected. These blades are subjected to alternating stresses, steady steam bending and severe centrifugal loads. For the above mentioned, a study was carried out on a blade of the last LP stage. In this work, the fatigue analysis of steam turbine blades was performed; crack initiation and propagation in blades were also analyzed under normal operation and at resonance conditions. The results showed that the crack initiation and crack propagation occur in fewer cycles under resonance conditions. When a crack appears it causes changes in the blade stiffness and if in addition, the blade is working under resonance conditions, their natural frequencies and the blade material decrease its fatigue strength. Highlights: Natural frequency decreases after appear of crack and your propagation. Vibration amplitude multiplies at resonance conditions. Crack propagation requires a less number of cycles in resonance conditions. Fatigue strength decreases at resonance conditions as compared to normal operation. Useful life in blades reduces under resonance conditions.